Tinjauan Yuridis terhadap Penggunaan Jasa Pihak Ketiga (Debt Collector) dalam Menagih Kredit Bermasalah pada PT Adira Dinamika Multifinance TBK - Kasirinus Jee Lua; Anak Agung Sagung Laksmi Dewi; Ni Made Puspasutari Ujianti (Jurnal Preferensi Hukum, 2021)
The use of third party services by financing company PT Adira Dinamika Multifinance through a third party Service Company (debt couecton to perform a collection function for consumers or debtors who are difficult to collect by being declared in default. Regulations for the use of third party services by financing companies are regulated in POJK No. /POJK.05/2018 concerning the Implementation of Business Financing Companies, where financing companies can collaborate with other parties (third party services) with the aim of collecting non-performing loans., The consequences of collaboration between third party services and financing companies to collect non-performing loans that the finance company is fully responsible for the cooperation carried out if there is an act that violates the law in accordance with POJK Number 35 / POJK.05 / 2018. However, if the financing company has carried out the prescribed procedure and the third party service continues to commit acts against the law, then the liability will be borne by the third party's services in order to collect non-performing loans. This research uses normative legal research. The technique of collecting legal materials in this study is to collect from literature studies using documentary / recording techniques obtained related to primary, secondary, and tertiary legal materials